Nutrient Dense, Low-Cost Foods Can Improve the Affordability and Quality of the New Zealand Diet-A Substitution Modeling Study - Starck CS; Blumfield M; Keighley T; Marshall S; Petocz P; Inan-Eroglu E; Abbott K; Cassettari T; Ali A; Wham C; Kruger R; Kira G; et al. (MDPI (Basel, Switzerland), 2021)
The high prevalence of non-communicable disease in New Zealand (NZ) is driven in part by unhealthy diet selections, with food costs contributing to an increased risk for vulnerable population groups. This study aimed to: (i) identify the nutrient density-to-cost ratio of NZ foods; (ii) model the impact of substituting foods with a lower nutrient density-to-cost ratio with those with a higher nutrient density-to-cost ratio on diet quality and affordability in representative NZ population samples for low and medium socioeconomic status (SES) households by ethnicity; and (iii) evaluate food processing level. Foods were categorized, coded for processing level and discretionary status, analyzed for nutrient density and cost, and ranked by nutrient density-to-cost ratio. The top quartile of nutrient dense, low-cost foods were 56% unprocessed (vegetables, fruit, porridge, pasta, rice, nuts/seeds), 31% ultra-processed (vegetable dishes, fortified bread, breakfast cereals unfortified <15 g sugars/100 g and fortified 15–30 g sugars/100 g), 6% processed (fruit juice), and 6% culinary processed (oils). Using substitution modeling, diet quality improved by 59% and 71% for adults and children, respectively, and affordability increased by 20–24%, depending on ethnicity and SES. The NZ diet can be made healthier and more affordable when nutritious, low-cost foods are selected. Processing levels in the healthier, modeled diet suggest that some non-discretionary ultra-processed foods may provide a valuable source of low-cost nutrition for food insecure populations.
Copyright: © 2021 by the authors.
Keywords: cost and cost analysis; diet; economic models; ethnic groups; food quality; food security; nutrients; socioeconomic factors; Adult; Child; Costs and Cost Analysis; Diet; Energy Intake; Fast Foods; Humans; New Zealand; Nutrients